Hugo [videorecording (DVD)] - Scorsese, Martin; Scorsese, Martin; Kingsley, Ben, 1943-; Baron Cohen, Sacha, 1971-; Butterfield, Asa, 1997-; Moretz, Chloë, 1997-; Winstone, Ray, 1957-; Mortimer, Emily; Lee, Christopher, 1922-2015; Selznick, Brian (Paramount Home Entertainment, 2012)
Tells the tale of an orphan boy living a secret life in the walls of a Paris train station. When Hugo encounters a broken machine, an eccentric girl, and the cold, reserved man who runs the toy shop, he is caught up in a magical, mysterious adventure that could put all of his secrets in jeopardy.